Incorporation of Nurse Initiated Management of Antiretroviral Treatment course within the undergraduate nursing programme North West province - Kabelo S. Bonokoane; Jeanettte M. Sebaeng; Seepaneng S. Moloko-Phiri (AOSIS, 2023)
Background: According to the 90-90-90 strategy, the focus is on 90% of people living with HIV and/or AIDS knowing their HIV status, initiated on antiretroviral treatment and achieving viral suppression. The challenge is that only 74% of people living with HIV and/or AIDS are on antiretroviral treatment, and HIV mortality still occurs. Literature recommends the incorporation of a Nurse Initiated Management of Antiretroviral Treatment (NIMART) course within the undergraduate nursing programme to capacitate new nurses to manage people living with HIV and/or AIDS immediately after completion of their training. However, the NIMART course is still not incorporated, and there is dearth of information on this topic in North West Province (NWP). Aim: To explore and describe nurse educators' perceptions regarding the incorporation of NIMART course within the undergraduate nursing programme in NWP. Setting: The setting of this research study was nursing education institutions of the NWP. Methods: Phenomenography qualitative research design was followed. Twelve nurse educators underwent purposive selection and unstructured individual interviews were conducted. The research co-coder verified the findings. There were ethical considerations and trustworthiness maintained throughout the study. Results: Main themes that emerged in this study depicted benefits and challenges associated with NIMART course incorporation within the undergraduate nursing programme as stated in Table 1. Conclusion: This study concluded that NIMART course incorporation within the undergraduate nursing programme is a good and relevant idea, which requires human and non-human resources. Contribution: The study contributed new knowledge on how nurse educators perceive the NIMART course incorporation within the undergraduate nursing programme in NWP.